EDUKASI KEBERSIHAN DIRI SAAT MENSTRUASI DALAM MENINGKATKAN PENGETAHUAN REMAJA PUTERI DI KELURAHAN BATANG ARAU KECAMATAN PADANG SELATAN KOTA PADANG - Anggela Pradiva Putri; Aulia Nur Afifah; Diva Zulvia; Faddila Raudatul Usmi; Ramadhani Nurul Mahmudah (BULETIN ILMIAH NAGARI MEMBANGUN, 2024)
Knowledge about personal hygiene and reproductive health care during menstruation is crucial for adolescents. This is related to the comfort of adolescents during menstruation. This article discusses personal hygiene during menstruation, reproductive tract diseases during menstruation, nutrition for smooth menstruation, reproductive age during menstruation, signs of abnormal menstruation, HIV in menstruating women, and the relationship between menstruation and reproductive health in the elderly. The aim of this activity is to enhance the in-depth knowledge of adolescent girls in Batang Arau Village, South Padang District, Padang, on how to maintain reproductive organ hygiene during menstruation. The method used in this activity includes lectures and Q&A sessions with the target audience. Additionally, pretest and posttest questionnaires were administered to assess the impact of the educational material. The activities consisted of counseling sessions targeting adolescents in Batang Arau Village, South Padang District, Padang. The results of this activity, obtained from statistical tests using the gain score test, showed an increase in knowledge from pretest to posttest, indicating a shift from low to moderate levels. Based on the frequency distribution table of pretest and posttest questions, it can be concluded that there were 4 questions with high effectiveness, 6 questions with moderate effectiveness, and 3 questions with low effectiveness. The conclusion from the activity targeting adolescents is that it was able to increase their knowledge regarding personal hygiene during menstruation.